Performance Measurement of Soasio Tidore Hospital from The Balanced Scorecard - Irfan Zam Zam; Kasim Sinen (Yayasan Riset dan Pengembangan Intelektual, 2023)
The purpose of this study was to determine the performance of the Soasio general hospital in a balanced scorecard perspective. This research is quantitative descriptive research. The operational variable of this research is performance measurement with indicators of four perspectives in the balanced scorecard, namely financial perspective, customer perspective, internal business process perspective, learning and growth perspective. The data sources used in this research are primary and sequential data. The data analysis technique used is descriptive analysis. The results showed that in the financial perspective the effectiveness ratio in achieving revenue was not effective.